African swine fever virus ubiquitin-conjugating enzyme pI215L inhibits IFN-I signaling pathway through STAT2 degradation - Riera, Elena; García-Belmonte, Raquel; Madrid, Ricardo; Pérez-Núñez, Daniel; Revilla, Yolanda (Frontiers in Microbiology, 2023)
African swine fever virus (ASFV) is the causative agent of one of the most lethal diseases affecting domestic pig and wild boar, which is endangering the swine industry due to its rapid expansion. ASFV has developed different mechanisms to evade the host immune response, including inhibition of IFN-I production and signaling, which is a key element in the cellular antiviral response. Here we report a novel mechanism of evasion of the IFN-I signaling pathway carried out by the ASFV viral protein I215L through the ubiquitination and proteasomal degradation of STAT2. In ectopic experiments and during ASFV infection, immunofluorescence, co-immunoprecipitation and nucleus-cytoplasm fractionation revealed interaction and colocalization of STAT2 and pI215L. Remarkably, the data obtained in this study involve, for the first time, the E2-ubiquitin-conjugating enzyme activity of pI215L in the immune response modulation, since expression of the catalytic mutant (I215L-C85A) did not inhibit the induction of the IFN-I response genes (ISGs) ISG15 and IFIT1, nor the activity of the IFN-I-stimulated response element (ISRE). Furthermore, we confirmed that STAT2 degradation by pI215L is dependent on its catalytic activity, since expression of the pI215L-C85A mutant did not affect STAT2 levels, compared to the wild-type protein. Yet, our data reveal that the interaction of pI215L with STAT2 does not require the integrity of its catalytic domain since the pI215L-C85A mutant co-immunoprecipitates with STAT2. All these findings identify the E2-ubiquitin-conjugating activity of pI215L as a viral mechanism to evade the host immune response.